The Community Rehabilitation Assessment: patient and clinician-reported outcomes in ambulatory rehabilitation - Turcotte, Luke Andrew; McArthur, Caitlin; Levy, Charissa; Ho, Rebecca; Hirdes, John P.; Berg, Katherine (Frontiers in Rehabilitation Sciences, 2023)
Objectives: The interRAI Community Rehabilitation Assessment (CRA) is a comprehensive health assessment designed to collect essential health and function information for rehabilitation care planning, benchmarking, and evaluation of clinic and home-based programs. A portion of the CRA is completed through patient self-report. The objective of this study was to demonstrate how the CRA can be used to describe the baseline clinical characteristics of patients participating in ambulatory rehabilitation programs and measure change across numerous domains of function, health, and wellbeing over time. Design: Cohort study. Setting and Participants: In total, 709 patients were assessed with the CRA across 25 ambulatory clinics in Ontario, Canada between January 1st, 2018, to December 31st, 2018. We examined sub-groups of patients receiving rehabilitation following stroke (n = 82) and hip or knee total joint replacement (n = 210). Methods: Frequency responses and means were compared between admission and discharge from the ambulatory rehabilitation programs. Measures of interest included self-reported difficulty in completing instrumental activities of daily living, locomotion, fear of falling, and pain. Results: Significant improvement relative to at admission was detected for the overall cohort and both sub-samples on individual instrumental activities of daily living, stair difficulty, use of mobility aides, distance walked, fear of falling, and pain. Conclusions and Implications: The standardized and comparable information collected by the CRA is expected to provide clinicians, clinic, and health system administrators with essential health and function information that can be used for care planning, benchmarking, and evaluation.